Zoonotic Vectorborne Pathogens and Ectoparasites of Dogs and Cats in Eastern and Southeast Asia - Colella, Vito; Nguyen, Viet L.; Tan, Do Y.; Lu, Na; Fang, Fang; Zhijuan, Yin; Wang, Jiangwei; Liu, Xin; Chen, Xinghui; Dong, Junyan; Nurcahyo, Wisnu; Hadi, Upik K.; et al. (Emerging infectious diseases, 2020)
To provide data that can be used to inform treatment and prevention strategies for zoonotic pathogens in animal and human populations, we assessed the occurrence of zoonotic pathogens and their vectors on 2,381 client-owned dogs and cats living in metropolitan areas of 8 countries in eastern and Southeast Asia during 2017-2018. Overall exposure to ectoparasites was 42.4% in dogs and 31.3% in cats. Our data cover a wide geographic distribution of several pathogens, including Leishmania infantum and zoonotic species of filariae, and of animals infested with arthropods known to be vectors of zoonotic pathogens. Because dogs and cats share a common environment with humans, they are likely to be key reservoirs of pathogens that infect persons in the same environment. These results will help epidemiologists and policy makers provide tailored recommendations for future surveillance and prevention strategies.